Multi-omics exploration of the factors influencing feather coverage in laying hens - Li, Xin; Shen, Xiaohui; Wang, Xiaoliang; Yan, Yao; Liu, Wei; Zhan, Kai; He, Daqian; Yang, Changsuo; Yan, Huaxiang; Yao, Junfeng (Frontiers in Animal Science, 2025)
ObjectiveThis study aimed to elucidate the molecular and microbial mechanisms underlying feather coverage in laying hens, with implications for understanding epithelial homeostasis and potential translational applications in tissue regeneration. By integrating multi-omics approaches, we sought to identify key genetic and microbial determinants of feather morphology and their synergistic effects on host physiology.MethodsA retrospective analysis was conducted on 400 laying hens classified into high (H) and low (L) feather coverage groups using a standardized 4-point scoring system. Transcriptomic profiling of cecal tissue was performed via RNA sequencing, while gut microbiota composition was analyzed using 16S rRNA amplicon sequencing. Differential gene expression and pathway enrichment were assessed using DESeq2 and clusterProfiler. Microbial community structure was evaluated through LEfSe analysis, and interplay between host transcripts and microbiota was examined via coinertia analysis.ResultsKey findings revealed distinct microbial signatures in the L group, characterized by elevated Bacteroidetes (P < 0.01) and reduced Firmicutes (P < 0.01) abundance compared with the H group. Transcriptomic analysis identified dysregulation of pathways involved in epithelial remodeling (Wnt/β-catenin, TGF-β) and structural integrity (BMP and keratin family genes). Integration of multi-omics data demonstrated significant correlations between microbial composition and host gene expression (P < 0.05), highlighting the synergistic regulation of feather morphogenesis via microbial-metabolite crosstalk.ConclusionsThis study elucidates the intricate interplay between host genetics and gut microbiota in regulating feather coverage, providing insights into epithelial biology and potential therapeutic targets for tissue homeostasis disorders. The findings underscore the importance of microbiome modulation in optimizing physiological traits relevant to avian health and agricultural productivity.